Fecal occult blood test screening uptake among immigrants from Muslim majority countries: A retrospective cohort study in Ontario, Canada. (30th September 2019) - Vahabi, Mandana; Lofters, Aisha; Wong, Josephine Pui‐Hing; Ellison, Lisa; Graves, Erin; Damba, Cynthia; Glazier, Richard H.
Abstract: Background: Colorectal cancer (CRC) is the second and third highest cause of cancer deaths among Canadian men and women, respectively. Population‐based screening through fecal occult blood testing (FOBT) has been proven to be effective in reducing CRC morbidity and mortality. Although participation in Ontario's organized CRC screening program has been increasing steadily since 2008, its uptake remains low among recent immigrant populations despite the known benefits of screening. To promote participation in CRC screening, it is imperative to understand both individual and system level barriers and enablers. Although a number of immigrant and nonimmigrant factors have been associated with low participation, there is a dearth of knowledge related to the religious affiliation in CRC screening uptake. Our study is among the first to examine this issue in Ontario, one of the most ethnically diverse Canadian provinces and preferred settlement destinations for immigrants. Methods: We conducted a population‐based retrospective cohort study using linked health care administrative databases. Our cohort included Ontario residents, age 50‐74 who were eligible for FOBT from 1 April 2013 to 31 March 2015. Results: We found that immigrants from the Middle East and North Africa and Eastern Europe and Central Asia had the lowest rates of screening. Furthermore, being born in a Muslim‐majority country was associated with lower FOBT screening even after controlling for other confounders including world region and income (ie, overall adjusted relative risk (ARR) of screening 0.92 [95% CI 0.90‐0.93]). Moreover, being enrolled in a primary care model, having a female primary care provider and having an internationally trained physician were associated with increased screening among immigrants from Muslim‐majority countries. Conclusions: These findings can inform future efforts to improve screening uptake like: enhancing access to primary care providers and enrollment in primary care models, targeted FOBT education for male providers and providers not in a primary care model, development of culturally sensitive and appropriate educational materials, and use of interactive approaches for communication of cancer screening information. Abstract : The FOBT screening uptake was low among immigrants from Muslim‐majority country. Immigrants from the Middle East and North Africa and Eastern Europe and Central Asia countries were at high risk of under‐screening. FOBT uptake was lower for people with no primary care provider and high income. Having a female primary care provider and having an internationally trained physician were associated with higher FOBT use among immigrants from Muslim majority countries.